Adolescent Identity at the Crossroads: A Critical Analysis of Social Media’s Multifaceted Impact on Academic Self-Concept - Al-Zuriqat, Mai Hathal; Obeidat, Bushra (Journal of Research in Vocational Education, 2025)
Adolescence marks a pivotal stage where social media, academic pressures, and family dynamics intersect to shape mental health and relationships. This study investigates these connections by analyzing data from 300 adolescents (aged 16–19) across urban and rural settings, using the Mental Health Scale and Family Environment Scale. Through a 3×2×2 factorial design and three-way ANOVA, results reveal that higher academic achievement correlates with better mental health and family environments, while excessive social media use negatively affects both. Gender differences also emerged, with boys reporting higher mental health scores than girls. These findings underscore the need for balanced digital habits and supportive family structures to foster adolescent well-being.